2013
DOI: 10.1155/2013/317185
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Thermocycling Process on the Dislodgement Force of Different Endodontic Cements

Abstract: To evaluate the effects of thermocycling (500 cycles, 5°C/55°C) on the push-out bond strength of calcium silicate based cements including WMTA, Nano-WMTA, and Bioaggregate to root dentin. Forty-eight dentin slices were prepared and divided into 3 groups (n = 16) and filled with Angelus WMTA, Nano-WMTA, or Bioaggregate. After incubation, half of the samples were thermocycled while the other half remained untreated. Push-out bond strength was calculated, and the modes of the bond failures were determined by SEM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
4
17
0
2
Order By: Relevance
“…Corrosion, the graded degradation of materials by electrochemical attack, is of concern particularly when orthodontic appliances are placed in the hostile electrolytic environment provided by the human mouth [36]. Investigators have shown that thermocycling regimen comprising a minimum of 500 cycles in water between 5 and 55°C is an appropriate artificial aging test [26,35]. The results of the current study revealed that thermocycling has a significant effect on the release of Ni from orthodontic appliances.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Corrosion, the graded degradation of materials by electrochemical attack, is of concern particularly when orthodontic appliances are placed in the hostile electrolytic environment provided by the human mouth [36]. Investigators have shown that thermocycling regimen comprising a minimum of 500 cycles in water between 5 and 55°C is an appropriate artificial aging test [26,35]. The results of the current study revealed that thermocycling has a significant effect on the release of Ni from orthodontic appliances.…”
Section: Discussionmentioning
confidence: 66%
“…Atomic adsorption spectrometer analysis is an effective, dependable, and feasible method to evaluate the amount of ion released from orthodontic wires in aqueous solutions [27,33]. It has been reported that temperature changes influence the physical and chemical properties of dental materials and most orthodontic appliances [22,24,26]. Thus, the current study aimed to evaluate the effect of pH changes and thermocycling, as the two main factors that change many times during the day after each meal and drink, on the amount of Ni released from orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nano WMTA showed significant improvements in the physiochemical properties of CSCs such as setting time, microhardness (17), push-out bond strength (18, 19), compressive strength (20), osseous reaction (21), and resistance in acidic environments (22). …”
mentioning
confidence: 99%